2019
DOI: 10.1111/phn.12600
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to receive influenza vaccination during pregnancy and associated factors among pregnant women in Taiwan

Abstract: Objective: This study was aimed to assess the willingness to receive prenatal influenza vaccine and explore its associated factors among pregnant women in Taiwan. Design and Sample:The study population included pregnant women who received prenatal care from five private hospitals/clinics during 2017-2018 influenza season. Measurements:Collected data, including demographics, health-relevant factors, as well as knowledge and attitudes regarding influenza and its vaccine, were analyzed using chi-square tests, Fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
5
9
1
Order By: Relevance
“…This situation may be attributed to the particularity of their work. Participants who had been vaccinated against influenza in the past were more willing to receive the SARS-CoV-2 vaccine, thereby suggesting that a secure vaccination experience of the viral vaccine was sufficient to make participants confident about being vaccinated, which was consistent with a previous research [17].…”
Section: Discussionsupporting
confidence: 85%
“…This situation may be attributed to the particularity of their work. Participants who had been vaccinated against influenza in the past were more willing to receive the SARS-CoV-2 vaccine, thereby suggesting that a secure vaccination experience of the viral vaccine was sufficient to make participants confident about being vaccinated, which was consistent with a previous research [17].…”
Section: Discussionsupporting
confidence: 85%
“…This may result from pregnant women’s higher level of perceived susceptibility and severity than the general population, for fearing that influenza infection during the COVID-19 period was harmful to both their health and their fetus. The acceptance rate of our study during the COVID-19 pandemic was also higher than the acceptance rate of influenza infection among pregnant women in Taiwan in 2018 (64.5%) [ 18 ] and that in Thailand in 2015 (41.8%) [ 24 ], indicating that women may address higher attention and awareness to their and their fetus’ health during the global pandemic that has caused global public health emergency and massive impact on social economy. Only 8.3% of the pregnant women in our survey had a history of influenza vaccination.…”
Section: Discussionmentioning
confidence: 62%
“…PASS software 14.0 (NCSS LLC., Kaysville, U.T., USA) was used to calculate the sample size. According to extant literature, the rate of influenza vaccination among pregnant women in Taiwan province in our country was 64.5% [ 18 ]. Set the alpha as 0.05, the confidence interval width as 0.1p, the sample size was 352 for each province when using the exact (Clopper-Pearson) method for calculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It reflects people's vaccination intention and behavior, and it supports the design and evaluation of tailored interventions that aim to improve vaccination coverage (14). A growing literature has shown that the concerns regarding the safety of rapidly developed vaccines (11), mistrust in biomedical research (15), lack of relevant knowledge (16,17), fear of adverse events (18), and lack of recommendations (19) contribute to COVID-19 and influenza vaccine hesitancy. During the COVID-19 pandemic, it is critical to initiate targeted measures to address vaccine hesitancy and improve vaccine acceptance, to promote vaccination on a large scale.…”
Section: Introductionmentioning
confidence: 95%